Human Pcf11 enhances degradation of RNA polymerase II-associated nascent RNA and transcriptional termination. - West, S; Proudfoot, N (2008)
The poly(A) (pA) signal possesses a dual function in 3' end processing of pre-mRNA and in transcriptional termination of RNA polymerase II (Pol II) for most eukaryotic protein-coding genes. A key protein factor in yeast and Drosophila Pol II transcriptional termination is the 3'-end processing factor, Pcf11. In vitro studies suggest that Pcf11 is capable of promoting the dissociation of Pol II elongation complexes from DNA. Moreover, several mutant alleles of yeast Pcf11 effect termination in vivo. However, functions of human Pcf11 (hPcf11) in Pol II termination have not been explored. Here we show that depletion of hPcf11 from HeLa cells reduces termination efficiency. Furthermore, we provide evidence that hPcf11 is required for the efficient degradation of the 3' product of pA site cleavage. Finally, we show that these functions of hPcf11 require an intact pA signal.